KAJIAN PEMANGKASAN TUNAS APIKAL DAN PEMUPUKAN KNO3 TERHADAP HASIL TANAMAN TOMAT - Maria Klara Salli; Yopy Imanuel Ismael; Yosefina Lewar (Partner, 2016)
Apical dominance on tomato crops impact on its lateral buds dormancy, it needs to be reduced by prunning the apical portion of the crop. Timeliness of prunning will affect the growth of lateral buds and its results as well. Lateral buds growth potential to become productive branches that will produce more flowers and fruits. The growth occurs when not followed by proper fertilization will lead to decreased fruit production. Nutrient that regulates flowering and fruiting is potassium, such as KNO3. Research carried out in field of State Agriculture Polytechnic of Kupang from July until November 2015. The results showed that a). The time prunning apical buds at 7 HST (days after planting), affect both the amount of production branches (6.7917), the number of fruit crops and plots (36.8333 and 464.83) and fruit weight per plot (17579.2 kgs) of tomatoes; b). KNO3 dose of 10 g/ltr (K2) , had a good influenced on fruits quantities in each crop (33.222), fruits diametres (4.1189 cm) fruits amount and its weight in each plot (419.11 fruits and 17,331 kgs). Otherwise, that dose has not a significant different with KNO3 dose of 5 g/ltr (K1), so K1 is better for fertilizer use efficiently; c). There are interactions between time of apical buds prunning on 7HST with KNO3 dose of 5 g/ltr (K1P1) where weight of tomatoes in each crop are best (1,987.21 g). This results will contributes as science and technology information for tomato farmers, teaching materials enrichment and scientific article publication.Â Keywords : prunning, buds, apical, KNO3, tomatoÂ